Clinical Characteristics and Surgical Safety in Congenital Cataract Eyes with Three Pathological Types of Posterior Capsule Abnormalities. (23rd March 2020) - Ding, Xixia; Xiang, Linfeng; Wang, Qianwei; Wang, Dandan; Chang, Pingjun; Li, Zhangliang; Zhao, Yinying; Chu, Feixue; Ma, Chao; Zhao, Yun-e
Abstract : Purpose . To observe the clinical characteristics of 3 pathological types of posterior capsule abnormalities (PCAs) in congenital cataracts (CCs) and evaluate the surgical safety in these eyes. Methods . This study involved 239 children (367 eyes) with CC who underwent cataract surgery at the Eye Hospital of Wenzhou Medical University. All surgery videos were collected for detailed reviews. Intraoperative and postoperative complications (within 3 months) were all recorded. Results . The 3 pathological types of PCAs, namely, persistent fetal vasculature (PFV), posterior capsule defect (PCD), and posterior lenticonus (PLC), presented in 129 (35.1%) CC eyes, while 238 (64.9%) eyes were recorded as CC without PCA. The percentages of PFV, PCD, and PLC were 10.9%, 26.7%, and 5.4% in CC eyes ( n  = 367), respectively. The most common concomitant of PFV eyes was PCD (42.5%), and PFV was the most frequent (17.3%) one in PCD eyes. PLC was only associated with PFV (15%) and PCD (50%). The occurrence rates of surgical complications ranged from 0 to 5.4%, and no statistical difference was found between the eyes with and without PCA (all P > 0.05 ). Conclusions . PFV, PCD, and PLC play a very important role in the CCs. The effect of fetal vessels in PFV eyes might be an abnormally strong attachment on the posterior capsule, leading to PLC and PCD. Even in PCA patients, severe surgical complication can also be avoided with well-designed and skilled operation. This trial is registered with NCT03905044 at http://ClinicalTrials.gov .